The Effect of Using a Social Science Learning Module Based on Local Wisdom of Aceh Culture on Student Motivation and Learning Outcome - Arianti, Ayu; Novalita, Rahmi; Muharramsyah, Rambang (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to describe; 1) the effect of using modules on student learning motivation,2) the effect of using modules on student learning outcomes, and 3) the effect of using modules on studentmotivation and learning outcomes. This type of research is quasi-experimental research using a quantitativeapproach. The subjects of this research were 22 students in class IV of Bebesen 1 State Elementary School.This research design uses One Group Pretest-Posttest Design. Data collection techniques use observation,questionnaires and documentation. Simple linear regression analysis test analysis technique. The researchresults show that; a) there is a significant influence of the use of social science learning modules based onlocal Acehnese cultural wisdom on student learning motivation, b) there is a significant influence of the use of social science learning modules based on Acehnese local cultural wisdom on student learning outcomes, c)there is a significant influence use of social science learning modules based on Acehnese cultural wisdom onstudent motivation and learning outcomes.